The effect of cognitive-behavioral therapy on psychological distress in the mothers of preterm infants: a systematic review and meta-analysis - Leila Seiiedi-Biarag; Mojgan Mirghafourvand; Solmaz Ghanbari-Homayi (Taylor & Francis Group, 2020)
Introduction: The birth of a preterm infant has the potential to cause stress, anxiety, depression and Post-Traumatic Stress Disorder (PTSD) in mothers. Numerous interventions have been developed for the parents of preterm infants to deal with these problems. Cognitive-Behavioral Therapy (CBT) is a client-centered intervention for improving mental health and alleviating psychological distress by transforming unconstructive thoughts and behaviors. The present systematic review was conducted to evaluate the effect of CBT on anxiety, depression and PTSD (the primary outcomes) and stress (the secondary outcome) in the mothers of preterm infants. Methods: A search was carried out of all the articles published by 30 Sep. 2018 in English and Persian databases including Medline (via PubMed), Scopus, Embase (via Ovid), Web of Science, Psycinfo, Google Scholar, SID, Magiran and Iran Medex. The risk of bias was assessed for the studies based on the Cochrane Handbook. The meta-analysis results were reported as Standardized Mean Difference (SMD). The heterogeneity of the studies was examined using I2, T2 and Chi2. Results: Four clinical trials on 455 mothers with preterm infants were systematically reviewed. The meta-analysis results revealed a lower mean depression score in the CBT group compared to the controls (SMD = −0.45; 95% CI: −0.98 to 0.08), but this difference was not statistically significant (p = .09). The mean scores of PTSD (MD = −11.69; 95% CI: −19.45 to −3.94; p = .003) and anxiety (SMD = −0.38; 95% CI: −0.61 to −0.15; p = .001) were significantly lower in the CBT group too. Conclusion: CBT was effective in decreasing the level of PTSD and anxiety in the mothers of preterm infants. Due to the small number of included studies and the small sample size, clinical trials with large sample sizes and a low risk of bias are recommended to provide evidence for the implementation of interventions affecting psychological distress in the mothers of preterm infants in clinical settings.